Insights from Bacterial 16S rRNA Gene into Bacterial Genera and Predicted Metabolic Pathways Associated with Stool Consistency in Rectal Cancer Patients: A Proof of Concept. Issue 3 (July 2023) - Gonzalez-Mercado, Velda Janet; Lim, Jean; Aouizerat, Bradley
Purpose: To examine if gut microbial taxa abundances and predicted functional pathways correlate with Bristol Stool Form Scale (BSFS) classification at the end of neoadjuvant chemotherapy and radiation therapy (CRT) for rectal cancer. Methods: Rectal cancer patients ( n = 39) provideds tool samples for 16S rRNA gene sequencing. Stool consistency was evaluated using the BSFS. Gut microbiome data were analyzed using QIIME2. Correlation analysis were performed in R. Results: At the genus level, Staphylococcus positively correlates (Spearman's rho = 0.26), while Anaerofustis, Roseburia, Peptostreptococcaceae unclassified, Ruminococcaceae UBA1819, Shuttleworthia, Ca. Soleaferrea, Anaerostignum, Oscillibacter, and Akkermansia negatively correlate with BSFS scores (Spearman's rho −0.20 to −0.42). Predicted pathways, including mycothiol biosynthesis and sucrose degradation III (sucrose invertase), were positively correlated with BSFS (Spearman's rho = 0.03–0.21). Conclusion: The data support that in rectal cancer patients, stool consistency is an important factor to include in microbiome studies. Loose/liquid stools may be linked to Staphylococcus abundance and to mycothiol biosynthesis and sucrose degradation pathways.